Generation of functional cholangiocyte‐like cells from human pluripotent stem cells and HepaRG cells. Issue 2 (20th June 2014) - Dianat, Noushin; Dubois‐Pot‐Schneider, Hélène; Steichen, Clara; Desterke, Christophe; Leclerc, Philippe; Raveux, Aurélien; Combettes, Laurent; Weber, Anne; Corlu, Anne; Dubart‐Kupperschmitt, Anne
<x xml:space="preserve">Abstract</x> Cholangiocytes are biliary epithelial cells, which, like hepatocytes, originate from hepatoblasts during embryonic development. In this study we investigated the potential of human embryonic stem cells (hESCs) to differentiate into cholangiocytes and we report a new approach, which drives differentiation of hESCs toward the cholangiocytic lineage using feeder‐free and defined culture conditions. After differentiation into hepatic progenitors, hESCs were differentiated further into cholangiocytes using growth hormone, epidermal growth factor, interleukin‐6, and then sodium taurocholate. These conditions also allowed us to generate cholangiocytes from HepaRG‐derived hepatoblasts. hESC‐ and HepaRG‐derived cholangiocyte‐like cells expressed markers of cholangiocytes including cytokeratin 7 and osteopontin, and the transcription factors SOX9 and hepatocyte nuclear factor 6. The cells also displayed specific proteins important for cholangiocyte functions including cystic fibrosis transmembrane conductance regulator, secretin receptor, and nuclear receptors. They formed primary cilia and also responded to hormonal stimulation by increase of intracellular Ca2+. We demonstrated by integrative genomics that the expression of genes, which signed hESC‐ or HepaRG‐cholangiocytes, separates hepatocytic lineage from cholangiocyte lineage. When grown in a 3D matrix, cholangiocytes developed epithelial/apicobasal polarity and formed functional cysts and biliary ducts. In addition, we showed that cholangiocyte‐like cells could also be generated from human induced pluripotent stem cells, demonstrating the efficacy of our approach with stem/progenitor cells of diverse origins. Conclusion: We have developed a robust and efficient method for differentiating pluripotent stem cells into cholangiocyte‐like cells, which display structural and functional similarities to bile duct cells in normal liver. These cells will be useful for the in vitro study of the molecular mechanisms of bile duct development and have important potential for therapeutic strategies, including bioengineered liver approaches. (Hepatology 2014;60:700–714)